2006
DOI: 10.1038/ng1852
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Drosophila melanogaster genome at the nuclear lamina

Abstract: The nuclear lamina binds chromatin in vitro and is thought to function in its organization, but genes that interact with it are unknown. Using an in vivo approach, we identified approximately 500 Drosophila melanogaster genes that interact with B-type lamin (Lam). These genes are transcriptionally silent and late replicating, lack active histone marks and are widely spaced. These factors collectively predict lamin binding behavior, indicating that the nuclear lamina integrates variant and invariant chromatin f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

40
535
1
5

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 549 publications
(581 citation statements)
references
References 49 publications
40
535
1
5
Order By: Relevance
“…This study identified several hundred genes as lamin-associated genes and revealed that these genes lack active histone modifications and are late replicating (Pickersgill et al 2006).…”
Section: Association Of Genes With the Nuclear Periphery And Nuclear mentioning
confidence: 99%
“…This study identified several hundred genes as lamin-associated genes and revealed that these genes lack active histone modifications and are late replicating (Pickersgill et al 2006).…”
Section: Association Of Genes With the Nuclear Periphery And Nuclear mentioning
confidence: 99%
“…According to this hypothesis, the dissociation of OCT1 from the nuclear envelope has been shown to be associated with collagenase gene up-regulation during the cell-aging process (Imai et al, 1997). On the other hand, two recent genome-wide localization studies revealed that the association with nuclear lamina was mostly characterized by a repressive chromatin environment, devoid of active histone marks and RNA polymerase II binding activities (Pickersgill et al, 2006;Guelen et al, 2008). Of interest, one demonstrated SRY partner protein is KRAB-O, which by means of KAP-1 is able to recruit histone deacetylase and HP1 heterochromatin protein (Peng et al, 2009).…”
Section: Subcellular Localization Of the Proteinmentioning
confidence: 99%
“…Electron micrographs of eukaryotic nuclei show that, in most cells, condensed heterochromatin is enriched at the nuclear periphery (Reik, 2007;Ueda et al, 2014;Wu et al, 2005). Genome-wide mapping using DamID technology (Guelen et al, 2008;Pickersgill et al, 2006) or ChIP-seq (Sadaie et al, 2013;Shah et al, 2013, reviewed in Gruenbaum andFoisner, 2015) revealed that there are laminaassociated domains (LADs), genome regions of low gene density that are in contact with the lamina. In agreement with the characteristics of LADs as transcriptionally silent environments, repressive epigenetic histone modifications are commonly found at the nuclear periphery, including H3K9me2, H3K9me3, H3K27me2 and H3K27me3 (Eberhart et al, 2013;Kind et al, 2013;Wu et al, 2005;Yokochi et al, 2009).…”
Section: Introductionmentioning
confidence: 99%